Customer-Bank Relationship in Commercial Banks Operating in Albania - Lumanaj, Jasmina; Virtyt Lesha (European Journal of Multidisciplinary Studies, 2016)
Financial institutions with high performance are always looking to the needs and requirements of their clients, in order to survive and compete successfully in today’s dynamic environment of corporations. For this reason researchers have stressed repeatedly the importance of customer satisfaction, loyalty and customer-bank relationship. The aim of this study is to develop a better theoretical and practical understanding of the impact that quality of service has in customer-bank relationship. This study examines the perception of service quality by clients of commercial banks operating in Albania and the effect that this quality has in customer-bank relationship. Measuring the perception of service quality is based on SERVQUAL model proposed by Parasuraman, Zeithaml - Berry (1988), while the measurement of customer-bank relationship is made according to the model proposed by Ward - Dagger (2007). Results of this analysis indicate that the quality of service is an important prerequisite of customer-bank relationship. From this study it is clear that managers and decision-makers in commercial banks in Albania seek to improve the quality of service elements, which constitute the most significant contribution to the improvement and strengthening of the relationship.